2018
DOI: 10.1017/cts.2018.322
|View full text |Cite
|
Sign up to set email alerts
|

Respondent-driven sampling to recruit Latinos in a midwest micropolitan area: Lessons learned and recommendations for translational work

Abstract: Introduction Latinos constitute a hard-to-reach minority population in Iowa. Methods We used respondent-driven sampling (RDS) to supplement random digit dialing (RDD) to recruit Latinos for a community physical activity intervention. Results RDS yielded a 59% increase in Latino participation in just two months, with few demographic differences between RDS and RDD groups. Conclusions RDS may increase recruitment of underrepresented populations and strengthen community engagement; however, it is not a quic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Of the interventions and protocol/design papers describing interventions (Table 1), the studies were primarily focused on physical activity or exercise (n = 25) (44)(45)(46)(47)(48)(50)(51)(52)(53)(54)(55)58,59,(61)(62)(63)(64)(65)(66)(68)(69)(70)(71)(72)(73) with only 5 studies examining disease selfmanagement programs (43,49,56,57,60,67). Of the reviews included (Table 2), 1 focused on recruitment strategies used for disease self-management programs (78), and 7 summarized recruitment and/or retention strategies for physical activity or exercise interventions (21,(79)(80)(81)(82)(83)(84).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the interventions and protocol/design papers describing interventions (Table 1), the studies were primarily focused on physical activity or exercise (n = 25) (44)(45)(46)(47)(48)(50)(51)(52)(53)(54)(55)58,59,(61)(62)(63)(64)(65)(66)(68)(69)(70)(71)(72)(73) with only 5 studies examining disease selfmanagement programs (43,49,56,57,60,67). Of the reviews included (Table 2), 1 focused on recruitment strategies used for disease self-management programs (78), and 7 summarized recruitment and/or retention strategies for physical activity or exercise interventions (21,(79)(80)(81)(82)(83)(84).…”
Section: Resultsmentioning
confidence: 99%
“…Among physical activity or exercise interventions, a few studies targeted populations with arthritis, including osteoarthritis (58,73), rheumatoid arthritis (73), and FM (50). The majority of studies included primarily African American (44)(45)(46)(47)(48)51,52,54,55,59,(64)(65)(66) or Hispanic or Latino populations (53,54,62,66,69,71,72). The reviews of strategies used in physical activity/exercise interventions primarily focused on underserved or underrepresented (21,79,(82)(83)(84) or African American populations (80).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study cites that relying on RDS prolonged the recruitment process as most participants did not refer future participants and ones who did only referred one participant at most. Additionally, in a 2018 analysis that supplemented random digit dialling with RDS, researchers found that RDS was helpful in increasing numbers of their target population; however, there was not enough time allotted to reach their recruitment goals [28]. They cite their failure to recruit a sufficient number of productive seeds prior to RDS as a part of the reason they did not reach recruitment targets.…”
Section: Discussionmentioning
confidence: 99%